Extended-Spectrum Beta-Lactamase- and Carbapenemase-Producing Enterobacteriaceae Family of Bacteria from Diarrheal Stool Samples in Northwest Ethiopia - Worku, Minichil; Getie, Michael; Moges, Feleke; Mehari, Alem Getaneh (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. Resistance among the commensal flora is a serious threat because they are highly populated ecosystems like the gut, maybe a source of extraintestinal infections. Infections due to extended-spectrum beta-lactamase (ESBL)- and carbapenemase (CPM)-producing Enterobacteriaceae family of bacteria impose a major global issue because they are usually resistant to multiple antimicrobial agents. Data on the fecal ESBL- and CPM-producing group of bacteria in developing countries including Ethiopia are limited mainly due to resource constraints. Thus, this study aimed to determine the prevalence of multidrug-resistant (MDR)-, ESBL-, and CPM-producing Enterobacteriaceae family of bacteria from diarrheal stool samples at the University Hospital, Northwest Ethiopia. Materials and Methods. A hospital-based cross-sectional study was conducted involving a total of 384 study participants having gastrointestinal complaints from January to April 2019. A diarrheal stool sample was aseptically collected and inoculated on a MacConkey agar plate. After getting pure colonies, biochemical and antimicrobial susceptibility testing was done following standard microbiological techniques. ESBL production was screened using ceftazidime and cefotaxime and confirmed using a combined disk diffusion test. Carbapenemases were screened by meropenem disk and confirmed by the modified carbapenem inactivation method. Data were checked, cleaned, and entered using Epi Info version 7.1 and transferred to SPSS version 20 for analysis. Result. A total of 404 Enterobacteriaceae groups of bacteria were isolated from 384 diarrheal stool samples. The overall prevalence of fecal MDR-, ESBL-, and CPM-producing group of Enterobacteriaceae was 196 (48.5%), 66 (16.3%), and 4 (1%), respectively. Of the total ESBL-producing Enterobacteriaceae, E. coli (41/66 (62.1%)) and K. pneumoniae (18/66 (27.3%)) were the most predominant isolates. One half of CPE has been observed in Citrobacter species and the rest in E. coli (25%) and P. vulgaris (25%). Conclusion and Recommendation. Finding the high rate of ESBL-producing Enterobacteriaceae and CPE requires strict infection control measures and careful selection of empirical therapy in the study area. Therefore, active surveillance with large sample size and better infection prevention control is needed.